EMPOWERING ADOLESCENTS IN ORPHANAGES: UNVEILING LIFE MEANING THROUGH IKIGAI TRAINING - Huwae, Arthur; Srituka, Salsa Cheryl; Meisya, Angeline; Za’rani; Oktafia, Ika; Natasha, Neysa; Datuchtidha, Shofiatun; Giarto, Nicky Angelica; Tantami, Elisabeth Dian Kurnia; Tirta, Olivia Aldora Maria; Badar, Natalie Hizkia Christina; Aginda, Odelia Sabrina Putri; Lembang, Galdies Betsi; Gondokusumo, Aneta Larasati (Counsenesia Indonesian Journal Of Guidance and Counseling, 2023)
The challenges faced by adolescents growing up in orphanages have provided valuable life lessons and shaped their identities across physical, psychological, spiritual, and social dimensions. However, many orphaned teenagers experience a sense of meaninglessness due to the loss of hope for developing into quality individuals. This issue poses risks to their daily living necessities. Therefore, the provision of a tool, such as IKIGAI training, is essential to facilitate orphaned adolescents in finding meaning in life. The aim of this research is to assess the effectiveness of IKIGAI training in discovering life meaning among adolescents in the Salatiga orphanage. The research employs a quantitative experimental design with a one-group pretest-posttest design. Ten participants from the Salatiga orphanage were involved using purposive sampling. The study includes an IKIGAI training module and the Meaning in Life Questionnaire (MLQ) to measure pretest and posttest values of life meaning. Data analysis involves the Wilcoxon Signed Rank test. The results demonstrate that IKIGAI training effectively assists orphaned adolescents in finding meaning in life (Z value of 2.848 and significance of 0.000; p < 0.05). This indicates that the discovery of life's meaning is crucial for adolescents, contributing to a sense of worth, creative life values, learning from past experiences, and planning future life goals a significance attributed to the application of IKIGAI in daily life.